Yoga for symptom management in oncology: A review of the evidence base and future directions for research. Issue 12 (1st April 2019) - Danhauer, Suzanne C.; Addington, Elizabeth L.; Cohen, Lorenzo; Sohl, Stephanie J.; Van Puymbroeck, Marieke; Albinati, Natalia K.; Culos‐Reed, S. Nicole
Abstract : Because yoga is increasingly recognized as a complementary approach to cancer symptom management, patients/survivors and providers need to understand its potential benefits and limitations both during and after treatment. The authors reviewed randomized controlled trials (RCTs) of yoga conducted at these points in the cancer continuum (N = 29; n = 13 during treatment, n = 12 post‐treatment, and n = 4 with mixed samples). Findings both during and after treatment demonstrated the efficacy of yoga to improve overall quality of life (QOL), with improvement in subdomains of QOL varying across studies. Fatigue was the most commonly measured outcome, and most RCTs conducted during or after cancer treatment reported improvements in fatigue. Results also suggested that yoga can improve stress/distress during treatment and post‐treatment disturbances in sleep and cognition. Several RCTs provided evidence that yoga may improve biomarkers of stress, inflammation, and immune function. Outcomes with limited or mixed findings (eg, anxiety, depression, pain, cancer‐specific symptoms, such as lymphedema) and positive psychological outcomes (such as benefit‐finding and life satisfaction) warrant further study. Important future directions for yoga research in oncology include: enrolling participants with cancer types other than breast, standardizing self‐report assessments, increasing the use of active control groups and objective measures, and addressing the heterogeneity of yoga interventions, which vary in type, key components (movement, meditation, breathing), dose, and delivery mode. Abstract : Randomized controlled trials conducted both during and after cancer treatment provide evidence for the efficacy of yoga to improve quality of life and fatigue. Yoga has the potential to improve additional cancer‐related symptoms (eg, sleep, depression, anxiety, distress, cognition) and biomarkers of stress and inflammation/immunity, but further research is needed.